An Optical Chemical Sensor for Determination of Nickel in Water and Hydrogen Peroxide Samples - Saeed, Babaee; Shahram, Ghanbari Pakdehi; Akram, Sadat Nabavi (Journal of New Developments in Chemistry, 2016)
Application of nickel in different industries has been developed and so contamination of natural water is a great concern due to its potentially toxic effects on living beings. Therefore, fast monitoring of Ni2+ in aqueous samples is important. In this work, we fabricated a sensitive optical sensor for determination of nickel in mineral water samples and hydrogen peroxide solutions. The optode was prepared by incorporation of 1-(2-pyridylazo)-2-naphthol and sodium tetraphenylborate in a plasticized poly (vinyl chloride) membranes containing dioctyladipate as a plasticizer. The influence of several parameters such as pH, base matrix, solvent mediator and ligand concentration were optimized. Comparison the obtained results with previously reported sensors revealed that the proposed method, in addition to fast and simplicity, provided good linear range (1.70–85.20 µmol L-1) and low detection limit (0.17 µmol L-1). The precision (relative standard deviation) was better than 1.55% for 7 replicate determinations of 17.10 µmol L-1 of Ni in various membranes.
Keywords: Optical sensor; Nickel determination; Poly (vinyl chloride) membrane; Hydrogen peroxide.